The effects of prenatal HIV exposure on language functioning in Kenyan children: establishing an evaluative framework. - Alcock, K; Abubakar, A; Newton, C; Holding, P (BioMed Central, 2016)
Background HIV infection has been associated with impaired language development in prenatally exposed children. Although most of the burden of HIV occurs in sub-Saharan Africa, there have not been any comprehensive studies of HIV exposure on multiple aspects of language development using instruments appropriate for the population. Methods We compared language development in children exposed to HIV in utero to community controls (N = 262, 8–30 months) in rural Kenya, using locally adapted and validated communicative development inventories. Results The mean score of the younger HIV-exposed uninfected infants (8–15 months) was not significantly below that of the controls; however older HIV-exposed uninfected children had significantly poorer language scores, with HIV positive children scoring more poorly than community controls, on several measures. Conclusions Our preliminary data indicates that HIV infection is associated with impaired early language development, and that the methodology developed would be responsive to a more detailed investigation of the variability in outcome amongst children exposed to HIV, irrespective of their infection status.